Masalah Kurikulum dan Pembelajaran Jenjang Pendidikan Dasar; Studi Kasus di Kecamatan Paciran Kabupaten Lamongan - Raikhan Raikhan (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The purpose of this research is to find out the implementation of learning in the thematic curriculum at the elementary education level? Which includes knowledge about thematic learning and books or teaching materials used. Obstacles encountered during the implementation of thematic learning in determining models, media, and assessments in thematic learning in the Paciran district, Lamongan Regency. This research uses a type of qualitative research with a qualitative descriptive approach. The researcher made direct observations in the field to study in more depth, as a non-participant researcher. The results of this study not all of them understand the substance of the thematic curriculum, so that in implementation there are still many deficiencies, in the implementation many teachers are happy because they are suitable for the age of the child. , as well as supporting facilities for thematic models, including aspects of assessment which in implementation must assess all aspects of learning themes but the teacher must assess according to the basic competencies of the subjects included in each theme.